A NEW FORM OF FUNDS STATEMENT. - Kunze, Harry L. (The Accounting Review, 1940)
Abstract It may be said that accountants are not in accord as to the content and arrangement of funds statements. The form suggested here is an attempt to improve that situation. As indicated it is first necessary to decide what is wanted from the statement before a determination can be made on what to put into it. The point of view adopted in this article is that the statement of funds is in reality a statement of the values, which came into the current section of the balance sheet and what was done with these values. Changes in other sections of the balance sheet are brought into the statement only to the extent that they involved the working capital of the company. By showing the gross profit-and-loss figures which affect the net current assets, the statement is made more significant, and the awkward and confusing method of starting with the net profit and adding back depreciation and similar charges is avoided. To treat the net change in working capital simply as a difference between increases and decreases is much clearer than the treatment of the net change found in the balanced form of report. Finally, the heading of the statement should give the ordinary reader a good idea of what to expect in the body of the statement.